2020
DOI: 10.1186/s40001-020-00462-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, epidemiological, and laboratory characteristics of mild-to-moderate COVID-19 patients in Saudi Arabia: an observational cohort study

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) emerged from China in December 2019 and has presented as a substantial and serious threat to global health. We aimed to describe the clinical, epidemiological, and laboratory findings of patients in Saudi Arabia infected with SARS-CoV-2 to direct us in helping prevent and treat coronavirus disease 2019 (COVID-19) across Saudi Arabia and around the world. Materials and methods Clinical, epidemiological, laboratory, and radiological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
55
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 25 publications
11
55
2
2
Order By: Relevance
“…The binary logistic regression analysis used in our study quantitatively suggests that the COVID-19 patients who have age > 50 years, who are males, or who have history of HTN and/or DM may have up to 9-fold increased chances of mortality than those patients who are young, who are females and are nondiabetic and normotensive. This is in line with the previous reports that suggest similar correlation between mortality and these factors(2,3,4,5,6,7).…”
supporting
confidence: 93%
“…The binary logistic regression analysis used in our study quantitatively suggests that the COVID-19 patients who have age > 50 years, who are males, or who have history of HTN and/or DM may have up to 9-fold increased chances of mortality than those patients who are young, who are females and are nondiabetic and normotensive. This is in line with the previous reports that suggest similar correlation between mortality and these factors(2,3,4,5,6,7).…”
supporting
confidence: 93%
“…And the case fatality rate of COVID-19 is variable [ 7 , 8 ]. The clinical characteristics of the disease in Saudi Arabia is similar to other reported presentations [ [4] , [5] , [6] , 8 , 9 ].…”
Section: Introductionsupporting
confidence: 84%
“…COVID-19had been associated with tremendous medical challenges as well as societal and industrial interruption [ 1 ]. COVID-19 clinical presentation ranges from asymptomatic to severe disease [ [2] , [3] , [4] , [5] , [6] ]. And the case fatality rate of COVID-19 is variable [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has a spectrum of presentations from asymptomatic cases to severe disease requiring intensive care unit admission [ 6 , [21] , [22] , [23] ]. The current study showed that 59% of the patients included in the home monitoring program were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%